Pengaruh Strategi Reading Questioning And Answering(RQA) Dipadukan Dengan Think Pair Share (Tps) TerhadapHasil Belajar Siswa Kelas VIII SMP Negeri 2 Colomadu PadaMateri Sistem Peredaran Darah Tahun Pelajaran 2015/2016 - Safitri, Dewi; , Drs. Djumadi, M.Kes (2016)
This research aim to know influence of strategy Reading Questioning and Answering combine Think Pair Share through the result of student learning toward student class VIII SMP N 2 Colomadu years 2015/2016. It used Pretest Postest Only Control Group Design quasi experiment method. This research sample is class VIII A for experiment class and VIII B for control class. The data collecting used instrument of learning result test in multiple choice consist of 35 questions. Based on the analyzed data, the differences between both classes were significant. The conclusion are taken from the value of hypothesis test using t-test for both posstest scores. The result is significant score = 0,026 at significant level 5% and it means significant score< significant level (0.026<0.05). And there fore it shows befound influence of strategy Reading Questioning and Answering combine Think Pair Share through the result of student learning.